Relationship of the American Heart Association's Impact Goals (Life's Simple 7) With Risk of Chronic Kidney Disease: Results From the Atherosclerosis Risk in Communities (ARIC) Cohort Study - Casey M. Rebholz; Cheryl A. M. Anderson; Morgan E. Grams; Lydia A. Bazzano; Deidra C. Crews; Alex R. Chang; Josef Coresh; Lawrence J. Appel (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundAs part of its 2020 Impact Goals, the American Heart Association developed the Life's Simple 7 metric for cardiovascular health promotion. The relationship between the Life's Simple 7 metric and incident chronic kidney disease (CKD) is unknown. Methods and ResultsWe estimated the association between Life's Simple 7 and incident CKD in 14 832 Atherosclerosis Risk in Communities study participants. Ideal levels of Life's Simple 7 health factors were the following: nonsmoker or quit >1 year ago; body mass index <25 kg/m2; ≥150 minutes/week of physical activity; healthy dietary pattern (high in fruits and vegetables, fish, and fiber‐rich whole grains; low in sodium and sugar‐sweetened beverages); total cholesterol <200 mg/dL; blood pressure <120/80 mm Hg; and fasting blood glucose <100 mg/dL. At baseline, mean age was 54 years, 55% were women, and 26% were African American. There were 2743 incident CKD cases over a median follow‐up of 22 years. Smoking, body mass index, physical activity, blood pressure, and blood glucose were associated with CKD risk (all P<0.01), but diet and blood cholesterol were not. CKD risk was inversely related to the number of ideal health factors (P‐trend<0.001). A model containing the Life's Simple 7 health factors was more predictive of CKD risk than the base model including only age, sex, race, and estimated glomerular filtration rate (Life's Simple 7 health factors area under the ROC curve: 0.73, 95% CI: 0.72, 0.74 versus base model area under the ROC curve: 0.68, 95% CI: 0.67, 0.69; P<0.001). ConclusionsThe AHA's Life's Simple 7 metric, developed to measure and promote cardiovascular health, predicts a lower risk of CKD.